Comparative Pharmacognostic and Powder Microscopic Studies of the Bark of Four Ficus Species (Nalpamaram) (International Journal of Ayurveda and Pharma Research, 2023)
Nalpamaram is widely used in traditional Ayurvedic system for the treatment of several ailments. It is very effective for the treatment of skin diseases like pigmentation, wrinkles and dark circles. This has a brown texture and a unique aroma. Nalpamaram is a mixture of four plant species of the family Moraceae - Ficus religiosa (Asvattha), Ficus benghalensis (Nyagrodha), Ficus racemosa (Udumbara) and Ficus microcarpa (Plaksah). The barks of the species are usually interchanged or adulterated with other species of Ficus because of the limited knowledge in identification and differentiation. Therefore, a detailed comparative pharmacognostic evaluation of the four species has been carried out with the aim to establish the diagnostic keys of these important drugs based on the pharmacognostic and powder macroscopic profiles. Pharmacognostic study of all these shows differences in values. Total ash is low in F. racemosa and high in F. benghalensis Acid insoluble ash is low in F. benghalensis and high in F. racemosa. Water soluble extractive is low in F. benghalensis and high in F. racemosa. Alcohol soluble extractive is low in F. benghalensis and high in F. racemosa.  Unique identification features like stone cells and prismatic crystals of calcium oxalate were found in the powder of all four species. The information from the present study provide data which is useful for the development of suitable monograph, determining the quality and purity of a crude drug and laying down Pharmacopoeia standards for Nalpamaram.